Spatio-temporal variability in structure and diversity in a semi-natural mixed oak-hornbeam floodplain forest. (September 2019) - Grotti, Mirko; Chianucci, Francesco; Puletti, Nicola; Fardusi, Most Jannatul; Castaldi, Cristiano; Corona, Piermaria
Highlights: Repeated mapped tree measurements in 3 forest stands with different soil moisture. Traditional (non-spatial) measures integrated with spatial and functional measures. Traditional measures did not show significant differences in diversity among stands. Spatial and functional measures revealed pronounced diversity in the moister stand. Spatial and functional measures must be integrated in traditional forest inventory. Abstract: Mixed forests are particularly interesting for forest structure and diversity analyses, as higher complexity and diversity can be expected in these forests compared to pure ones. Integrating different approaches in the analyses of structure and diversity in these forests can provide complementary information on non-spatial, spatial and functional diversity patterns. The study aimed at evaluating the spatio-temporal dynamics in forest structure and diversity in a semi-natural mixed oak-hornbeam floodplain forest. All standing trees were mapped and inventoried in 1995, 2005 and 2016 in three 1-ha mixed forest stands, with different soil moisture regime (xeric, mesic, moist conditions). Traditional, non-spatial structure and diversity measures were coupled with spatially-explicit and functional diversity measures. Results indicated that the three stands showed limited variation in stand structure and similar non-spatial diversity attributes, despite the different species composition. Only the extension to spatial and functional analyses was able to reveal more pronounced differences of diversity patterns, as higher complexity, species mingling, and functional tree complementarity was observed in the moister stand. These findings support use of spatially-explicit measurements in traditional inventory measurement protocols to allow more refined analysis of diversity patterns. On the other hand, functional diversity can be easily implemented in diversity analyses, as it requires species abundance information (which is traditionally collected in forest inventory) and species-specific tree traits which can be inferred from literature.